AN OVERVIEW ON DOSAGE FORM: SUPPOSITORY - Jain, Anvesh; Panwar, Mangal Singh (Journal of Global Pharma Technology, 2025)
In this article we converse about various aspects of suppositories such as their introduction, formulations and therapeutic applications. Suppositories are those type of dosage forms that used to provide medication via the vaginal and rectal routes. Before the invention of suppository, liquid enema was used. Enema’s has a big disadvantage that it leaks out of the cavity where it is inserted. Therefore an alternate method of medication was needed and thus suppository was invented. Suppositories can be described as semi-solid dosage form to provide medications via rectal, vaginal routes where they will melt or dissolve and deliver localized or systemic action. Suppositories are preferred over other dosage form because it comes in different shapes and sizes. Suppositories are one of the very convenient modes for drug delivery. In this article we discuss the fundamental components of suppositories including suppository bases, along with the methods of preparation of suppository. This article also targets to fabricate descriptive information about the advancement of suppositories such as, Bi-layered Suppositories, Hollow Suppositories, Effervescent suppositories, etc. Keywords: Suppositories, Types of Bases, Methods of Preparation, Advancement in suppositories.